Dust Exposure and Respiratory Health Among Workers in Primary Coffee Processing Factories in Tanzania and Ethiopia - Bråtveit, Magne; Abaya, Samson Wakuma; Sakwari, Gloria; Moen, Bente E. (Frontiers in Public Health, 2021)
Introduction: In primary coffee factories the coffee beans are cleaned and sorted. Studies from the 80- and 90-ties indicated respiratory health effects among the workers, but these results may not represent the present status. Our aim was to review recent studies on dust exposure and respiratory health among coffee factory workers in Tanzania and Ethiopia, two major coffee producing countries in Africa. Methods: This study merged data from cross-sectional studies from 2010 to 2019 in 4 and 12 factories in Tanzania and Ethiopia, respectively. Personal samples of “total” dust and endotoxin were taken in the breathing zone. Chronic respiratory symptoms were assessed using the American Thoracic Society (ATS) questionnaire. Lung function was measured by a spirometer in accordance with ATS guidelines. Results: Dust exposure among male production workers was higher in Ethiopia (GM 12 mg/m3; range 1.1–81) than in Tanzania (2.5; 0.24–36). Exposure to endotoxins was high (3,500; 42–75,083) compared to the Dutch OEL of 90 EU/m3. The male workers had higher prevalence of respiratory symptoms than controls. The highest symptom prevalence and odds ratio were found for cough (48.4%; OR = 11.3), while for breathlessness and wheezing the odds ratios were 3.2 and 2.4, respectively. There was a significant difference between the male coffee workers and controls in the adjusted FEV1 (0.26 l/s) and FVC (0.21 l) and in the prevalence of airflow limitation (FEV1/FVC < 0.7) (6.3 vs. 0.9%). Among the male coffee workers, there was a significant association between cumulative dust exposure and the lung function variables FEV1 and FVC, respectively. Conclusions: The results suggest that coffee production workers are at risk of developing chronic respiratory symptoms and reduced lung function, and that the findings are related to high dust levels. Measures to reduce dust exposure should be targeted to factors identified as significant determinants of exposure.